ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДА ЖӘДИДЛИК ИДЕЯЛАРДЫҢ СӘЎЛЕЛЕНИЎИ - Давлетов, Б.А. (FAN va JAMIYAT, 2025)
The article provides an understanding of Jadidism. In the history of Karakalpak literature, the formation of Jadidism ideas is mentioned. Issues such as the opening of the first new method schools, the creation of textbooks, many works of art, and their distribution among the people were analyzed. The ideological and thematic orientations of the works of the representatives of Jadididist literature were studied based on the texts of the works.